Turner’s Syndrome in Adulthood and Cytogenetics - Hossain, F; Nahar, K N; Mahmoud, S; Islam, F A; Begum, N; Akhter, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Turner’s syndrome is a chronic disease of chromosomal aberration. The purpose of the study was to find out the accurate identification of cell line, which is critical for cytogenetic studies, genetic counseling, phenotypic studies carried out with few reconstructive procedures to plan future sexual and reproductive life. Methods: This study design was a prospective hospital based clinical study. In this study, ninety six patients were studied with secondary sex characters with relevant ultrasonogram findings and hormonal assay who underwent karyotyping in Bangabandhu Sheikh Mujib Medical University, Dhaka for a study period of ten years from October 1997 to October 2007. Results: Among 96 patients, 62.5 % of the patients were from 15-18 years. Four girls who were less than 15 years came with Turner’s and testicular stigmata. Twenty women aged more than 26 years presented with coital problems. Around 72.9% had no secondary sexual character, 20.83% had normal female type of secondary sex character, and 6.25% had virilizing type of secondary sexual character. Karyotyping of the cases revealed 72.9% (n = 70) had 45XO pattern, which belong to the Turner's stigmata and correlated well with the hormone profile. Whereas, 20.83% (n = 20) had 46XX pattern and 6.25% (n = 6) had 46XY pattern with testicular feminization syndrome with inguinal testis. Conclusions: About 60% of cases were in the 15-18 years age group. Most of the patients presented with no secondary sexual characteristics. 45XO chromosomal pattern was the most common presenting in 72.9% cases. DOI: http://dx.doi.org/10.3126/njog.v9i2.11744